Student Management System Development of Damya Deena Tuition Center (SPP Damya Deena) - Mohd, Ros Aida Yati; Ramli, Azizul Azhar (Applied Information Technology And Computer Science, 2022)
Damya Deena Tuition Center Student Management System (SPP Damya Deena) is a web-based system that works to facilitate student registration at Damya Deena Tuition Center. Currently, student registration is done using printed forms. However, the information management process for these forms becomes less efficient because it is not managed systematically using a computerized database. It cause difficuties while retrieving back the information and reporting. This method is very impractical as it can cause data loss. Looking at these weaknesses, the Student Management System of Damya Deen Tuition Center (SPP Damya Deena) was build. The Agile model is used as a methodology for the development of this system. The system is build Hypertext Preprocessor (PHP), Hypertext Mark-up Language (HTML) and MySQL database software. There are three users for this system which is administrators, teachers and students. The functions provided in this system are login, subject registration, list of students and teachers, student performance and fee payment. In general, this system was developed to help the Tuition Center manage the data more systematically. It is hoped that this system is successfully developed perfectly.